Taking Down the Wall : Transition and Inequality - Cevik, Serhan; Correa-Caro, Carolina (Washington, D.C. : International Monetary Fund, 2020)
This paper investigates the main determinants of income inequality in transition countries during the period 1990-2018. To this end, we address a major methodological challenge that lies at the core of the cross-country literature on income inequality: the potential endogeneity of income growth, which is largely ignored by most empirical studies. We adopt a two-pronged empirical strategy by (i) using trading partners' weighted average real GDP as an instrumental variable (IV), and (ii) estimating the model via the two-stage least squares (2SLS) approach for static models and the Generalized Method of Moments (GMM) estimator for dynamic models. Our empirical findings are consistent with the Kuznets curve that illustrates a nonlinear relationship between income inequality and the level of economic development. We also find that the redistributive impact of fiscal policy is statistically insignificant and taxation and government spending appear to have the opposing effects on income inequality in transition economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet